Cardiac conduction disturbances in patients with ankylosing spondylitis: results from a 5-year follow-up cohort study. Issue 2 (13th November 2019) - Bengtsson, Karin; Klingberg, Eva; Deminger, Anna; Wallberg, Hanna; Jacobsson, Lennart T H; Bergfeldt, Lennart; Forsblad-d'Elia, Helena
Abstract : Objectives: To describe electrocardiographic (ECG) development in patients with ankylosing spondylitis (AS) and identify associations between baseline characteristics and cardiac conduction disturbances (CCD) at 5-year follow-up. Methods: In a longitudinal cohort study, 172 patients (54% men, mean age (SD) of 50 (13) years at baseline) with AS underwent ECG, physical examination, questionnaires and laboratory testing at baseline and at 5-year follow-up. Descriptive statistics and univariate and age- and sex-adjusted logistic regression analyses were used. CCD included both atrioventricular and intraventricular blocks. Results: Twenty-three of the 172 patients (13.4%) had a CCD at follow-up. Eight patients had developed a new CCD and eight had normalised their ECG. In the age- and sex-adjusted analyses, CCD at baseline (OR 24.8, 95% CI 7.3 to 84.5), male sex (OR 6.4, 95% CI 2.0 to 20.8), history of anterior uveitis (OR 4.4, 95% CI 1.3 to 14.5), higher ASDAS-CRP (OR 2.3, 95% CI 1.3 to 4.0), greater waist circumference (OR 1.3, 95% CI 1.1 to 1.6, per 5 cm), and medication with antiplatelets (OR 7.0, 95% CI 1.5 to 31.8) and beta-blockers (OR 3.4, 95% CI 1.0 to 11.5) were associated with a CCD at follow-up. Higher age and longer symptom duration were highly correlated and were both associated with a CCD at follow-up. Conclusions: The presence of CCD in AS is in part dynamic and associated with both AS and non-AS characteristics. Our results suggest that patients especially prone to present with CCDs are older men with a previous CCD, longer symptom duration, higher AS disease activity, a history of anterior uveitis and medication reflecting cardiovascular disease.